NILAI-NILAI FILSAFAT DAN TASAWUF DALAM MENJAWAB TANTANGAN MASYARAKAT KONTEMPORER - Novianto, Fauzan Akbar; Saumantri, Theguh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Society follows the progress of the times marked by rapid advancements in media technology, economy, and information. However, these advancements have led modern society to face lifestyles and ways of thinking that ultimately harm society itself. The aim of this research is to find solutions for modern society, which has become engulfed in confusion, through the approaches of Sufism and philosophy. Using a qualitative literature review method, the author focuses on Al-Ghazali's Sufi theory and Herbert Marcuse's philosophical theory. This focus allows for an in-depth analysis of both figures and their thoughts. In addressing problems faced by modern society such as materialism, consumerism, and individualism, Al-Ghazali, with his ethical Sufi theory, offers qualities like asceticism (zuhud), contentment (qona’ah), and brotherhood (ukhuwwah). Similarly, Herbert Marcuse proposes various solutions such as restoring critical consciousness, enlightenment, and cultural movements. In an era of limitless technological advancement and information reception, the implementation of these solutions becomes increasingly important and necessary for modern society.